Composição e Distribuição Espaço-Temporal da Macrofauna Bêntica em um Estuário com Regime de Macromaré na Costa Amazônica Maranhense – Brasil - FERREIRA, Helen Roberta Silva (2018)
In this study the composition and spatial and temporal distribution of the benthic macrofauna in the Rio Perizes estuary (Maranhão - Brazil) were analyzed. Biological and environmental samples were collected at five sampling points along the estuary during the six months of September, October and November / 2016 (drought period) and February, March and April / 2017 (rainy season). Samplings were performed with a 682 cm 2 van Veen dredger type. At each collection point, environmental variables were measured to relate to the biological data. The environmental parameters temperature, pH, salinity, dissolved oxygen, saturation and transparency did not present a gradient along the sample points, however, they showed marked differences in temporal distribution. In total, 35,597 individuals belonging to 84 taxa were identified, corresponding to Insecta, Mollusca, Crustacea, Annelida, Nematoda, Nemertea, Sipuncula, Colembola, where the Polychaeta group presented higher richness, while Tanaidacea was more abundant. The temporal distribution of the benthic macrofauna was influenced by the variables salinity and rainfall. Oligochaeta and Tanaidacea stood out at all sampling points, Acari was abundant in the internal area of ​​the estuary, while the Ostracoda number was very high in the external area. The structure of the macrobenthic community differed in the composition of most of the estuarine studies, with expressive dominance of the Tanaidacea and Oligochaeta groups. The highest abundance of Tanaidacea is related to environments rich in fine sediments with presence of organic matter and its occurrence was determinant for distribution of the other species. The results indicated that the rainy season favored the establishment of the benthic community with increased diversity and equitability.